Analysis of Employee Morale at the Mojokerto City Communication and Informatics Office - Fildha Hibatur Rahma; Sulastri Irbayuni (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of work stress and work environment on the morale of all employees at the Mojokerto City Communication and Information Service. The total sample is 73 employees taken by the saturated sampling method. Data collection by conducting interviews and distributing questionnaires to all employees. The variables used by researchers include the variable Work Stress (X1) and the Physical Work Environment (X2) and the Work Spirit variable (Y). Using an analytical model in the form of Partial Least Square (PLS) to examine whether there is influence between constructs in order to assess prediction correlations between them. The outcomes of the study show that work stress does not contribute and the physical work environment contributes to employee morale.